Impact of the COVID-19 pandemic on knowledge, perceptions, and effects of telemedicine among the general population of Pakistan: A national survey - Tariq, Waleed; Asar, Muhammad Anas Tahseen; Tahir, Muhammad Junaid; Ullah, Irfan; Ahmad, Qasid; Raza, Ahmad; Qureshi, Mohsin Khalid; Ahmed, Ali; Sarwar, Muhammad Zarak; Ameer, Muhammad Atif; Ullah, Kaleem; Siddiqi, Haziq; et al. (Frontiers in Public Health, 2023)
Background: Telemedicine is the provision of healthcare services through information and communication technology with the potential to mobilize all facets of the health sector to prevent the spread of COVID-19, provide quality healthcare, protect patients, doctors, and the public from exposure to disease, and reduces the burden on the health care system. This study aims to identify knowledge, perceptions, willingness to use, and the impact of the COVID-19 pandemic on telemedicine awareness. Methods: A cross-sectional was conducted from May 27, 2020, to June 17, 2020, using the convenient sampling technique from the general population of Pakistan. Data was collected by designing an online questionnaire consisting of demographic information, knowledge, attitude perceptions, barriers, utilization, and the impact of the COVID-19 pandemic on telemedicine. Results: 602 participants included were included in the study, 70.1% had heard about telemedicine, 54.3% had a good understanding of the definition of "telemedicine," 81.4% had not used telemedicine in the past, 29.9% didn't know that telemedicine was available before the COVID-19 pandemic and 70.4% responded that COVID-19 pandemic had changed their attitudes towards telemedicine. Gender (p=0.017) and family income (p=0.027) had a significant association with the perception of the benefits of telemedicine. Conclusion: The knowledge and usage of telemedicine are lacking due to inadequate awareness and technology. The need of the hour is to maximize the application of telemedicine to overcome the deficiencies of the health care system. Hence, it is essential to increase awareness through various means and develop an appropriate infrastructure to attain maximum benefits from telehealth services.